Comparative Study of Physical and Chemical Activation of Coal Fly Ash as Potential Adsorbent Based on FTIR and XRD Analyses - Wayan Gracias; Radho Al Kausar; Ermin Riskiani (Universitas Diponegoro, 2026)
Coal fly ash is a combustion residue that demonstrates potential use an affordable adsorbent. However, the adsorption capacity is still limited if no modification is made, so the activation stage is crucial. The present work investigates the differences between physical and chemical activation on changes in the structure of coal fly ash. Physical activation was carried out through a calcination process at 400 °C within 2 hours, while chemical activation was carried out through a reflux process using a 2 M HCl solution at 50 °C for 6 hours period. The samples were characterized using infrared spectroscopy (FTIR) and X-ray diffraction (XRD) techniques. The obtained results clearly exhibit that physical activation did not cause significant structural changes. In contrast, chemical activation induces partial dealumination in the aluminosilicate framework, which is characterized by a shift in the silanol (Si–O) band from 995 cm⁻¹ to 1057 cm⁻¹ in the FTIR spectrum, as well as a decrease in mullite intensity and an increase in quartz dominance based on the XRD diffractogram as indicated by the proportion of quartz relative intensity to mullite from 1,000 in CFA to 1,099 and 1,505 respectively in CFAP and CFAC. These changes result in a more silica-rich surface with a higher density of silanol groups, thereby increasing the number of active sites for the adsorption process.